2022
DOI: 10.54101/acen.2022.3.8
|View full text |Cite
|
Sign up to set email alerts
|

The cerebrovascular, neuroprotective and antiarrhythmic properties of the anxiolytic fabomotizole

Abstract: Aim. To examine the cerebrovascular, neuroprotective and antiarrhythmic properties of fabomotizole (brand name Afobazole). Materials and methods. A comprehensive study of fabomotizole's effects on the blood supply, morphology and neuropsychology of the rat brain in various experimental disorders. We recorded cerebral blood flow and studied brain morphology in models of local permanent and global transient ischaemia, haemorrhagic brain damage, combined cerebrovascular and cardiovascular pathology, cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Further studies identified a new derivative of tropane acylhydrazone -acylhydrazone (2,3,4-trimethoxy-N'-(8-methyl-8-azabicyclo[3.2.1. ]octan-3-ylidene) benzo-hydrazide hydrochloride (LK-933), which along with cerebrovascular anti-serotonin activity also has anxiolytic and antiaggregatory activities Mirzoian et al 2020).…”
Section: Search For New Anti-ischemic Anti-migraine Preparationsmentioning
confidence: 99%
“…Further studies identified a new derivative of tropane acylhydrazone -acylhydrazone (2,3,4-trimethoxy-N'-(8-methyl-8-azabicyclo[3.2.1. ]octan-3-ylidene) benzo-hydrazide hydrochloride (LK-933), which along with cerebrovascular anti-serotonin activity also has anxiolytic and antiaggregatory activities Mirzoian et al 2020).…”
Section: Search For New Anti-ischemic Anti-migraine Preparationsmentioning
confidence: 99%